Peningkatan Status Gizi Melalui Pendidikan Kesehatan Metode Lomba Pada Anak Usia Prasekolah (Di TK PKK Parang 1 Desa Parang Kec. Banyakan Kab Kediri) - Maria Anita Yusiana; Sandy Kurniajati (Pelita Medika, 2021)
Background : Stunting is a growth disorder that describes the failure to achieve growth potential as a result of suboptimal health and/or nutritional status. The purpose of community service is to improve nutritional status through health education, competition methods for preschool age children at PKK Parang 1 Kindergarten, Parang Village, Kec. Banyakan, Kediri Regency. Method : The program of activities carried out is in the form of community service in the form of health education with the competition method, targeting preschoolers and parents in PPK Prang I Kindergarten with a total of 20 children. Measurement analysis by measuring Nutritional Status based on BB/U and TB/U, as well as mother's behavior in personal hygiene. Result : The results of the Phase I activity on April 30, 2021, there were 14 child targets by measuring the nutritional status and behavior of mothers in personal hygiene as well as health education using leaflets and question and answer methods with the theme Stunting, as well as giving vitamins, milk and snacks, and Phase 2 On 7 May 2021 there were 17 children, with activities measuring children's nutritional status and measuring mother's behavior in personal hygiene, as well as announcements of healthy children's competitions based on children's nutritional status and mother's behavior, as well as giving vitamins, milk and snacks. The results of the measurement of Nutritional Status based on BW/U obtained that there were 2 children (10%) who were very underweight and underweight, nutritional status based on TB/U (stunting) there were 2 children (10%) who were stunted. The results of the competition based on changes in mother's behavior and nutritional status of children obtained 3 winners of 1st place, 2nd place and 3rd place. Conclusion : Through community service, the incidence of stunting and nutritional status is less than 10% of children and the behavior of mothers with health education has increased.